Religious Expression of Young Muslim Women's Identity amid Diversity in Bali - Fajri Zulia Ramdhani (Sawwa: Jurnal Studi Gender, 2025)
Religious expression among minority groups often unfolds within complex negotiations between identity, social acceptance, and cultural diversity. This study explores the dynamics of religious expression among young Muslim women in Bali within the context of sociocultural diversity and the challenges of being a minority. Bali, as a global tourism destination, has a history of Muslim communities dating back to the 14th century coexisting with the Hindu majority. The research employs a descriptive-qualitative method, utilizing participant observation, in-depth interviews, focus group discussions (FGDs), and document analysis. Primary data were collected from young Muslim women, community leaders, and Islamic youth organizations in Bali. The results reveal that young Muslim women face significant challenges, including religious discrimination, social pressure in expressing their faith, limited access to religious education, difficulties in obtaining halal food, and religious conversion due to marital pressures. On the other hand, they utilize social media as a new space to express their religious identities. In interfaith interactions, young Muslim women demonstrate adaptability to local norms while facing tensions between religious identity and social demands. Theoretically, this research enriches the discourse on the relationship between identity, religious minorities, and religious expression in multicultural contexts such as Bali.